Out of School Children: Causes behind Primary Dropout - Shamas ul Deen; Rimsha Kamran (JIE, 2023)
The research aimed to determine the causes behind dropouts from primary level education in rural areas of Pakistan and reasons why out of school children prefer to be enrolled in Non-Formal Basic Education Institutions (NFBEIs). Government of Punjab has initiated non formal institutions to tackle the issue of high dropout by opening NFBEIs in different regions of the province. The study consisted on two phases. In the first phase, children were identified who had been dropped out of school. In the second phase reasons were found out of their being dropped out and the facilities available at the NFBEIs.